Millimeter-Precision Laser Rangefinder Using a Low-Cost Photon Counter - Eisele, Andreas (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2014)
In this book we successfully demonstrate a millimeter-precision laser rangefinder using a low-cost photon counter. An application-specific integrated circuit (ASIC) comprises timing circuitry and single-photon avalanche diodes (SPADs) as the photodetectors. For the timing circuitry, a novel binning architecture for sampling the received signal is proposed which mitigates non-idealities that are inherent to a system with SPADs and timing circuitry in one chip.